Compact Memory Implementations of the ML-DSA Post-Quantum Digital Signature Algorithm - Meneses, Rodrigo Duarte de; Teixeira, Caio; Henriques, Marco Aurélio Amaral (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2024: Anais Estendidos do XXIV Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2024)
This paper explores memory optimization techniques in the implementation of the Module-Lattice-Based Digital Signature Algorithm (ML-DSA) in the context of post-quantum cryptography. It shows how to achieve significant reductions in memory usage, and evaluates the trade-offs in computational speed. Moreover, it demonstrates how the secret (private) key can be managed to reduce significantly its storage requirements, thereby enhancing ML-DSA’s applicability in some resource-constrained environments.